Quarterly Plan Penambangan Nikel Tahun 2020 pada Pit X PT. Elit Kharisma Utama Menggunakan Software Maptec Vulcan 9.1 - Rihan Efendi; Dedi Yulhendra (Journals Mining Engineering : Bina Tambang, 2019)
Abstract. PT. Elit Kharisma utama is one of the private mining companies that are conducting laterite nickel mining in Desa Morombo, Kecamatan Lasolo, Kabupaten Konawe Utara, Provinsi Sulawesi Tenggara. The mining method used is an open pit. Currently PT. Elit Kharisma Utama has been mining the Yudhistira Pit and plans to open a new pit (Pit X) which is next to the Yudhistira Pit. Based on the estimated block model using inverse distance method obtained at Pit X amount of reserves is 201,992.2 bcm with an average Ni content is 1.69% according to consumer demand at a level of 1.5% Ni and stripping ratio of 1:3 can be mined in a single quarter in beginning in 2020 with a production target of 50,000 bcm per month. Based on the research it can be concluded that the total reserves at Pit X are feasible to be mined and meet the planned production targets.Keywords:  Reserve, Grade, Production, Overburden, Ore.